2018
DOI: 10.1016/j.ejon.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

It is important that the process goes quickly, isn't it?” A qualitative multi-country study of colorectal or lung cancer patients' narratives of the timeliness of diagnosis and quality of care

Abstract: Initiatives emphasising the timeliness of diagnosis and treatment are reflected in the ways some patients experience their care. However, these accounts were open to further contextualisation about what speed of healthcare processes meant for evaluating the quality of their care. Healthcare professionals could therefore be an important patient resource in providing reassurance and support about the timeliness of diagnosis or treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…Timely care also adds to patients’ quality of life and emotional well-being 24. In addition, patients’ descriptions of the quality of their care are closely related to the speed of their diagnosis and treatment; this is because they are concerned that longer waits might allow time for their cancers to grow 25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely care also adds to patients’ quality of life and emotional well-being 24. In addition, patients’ descriptions of the quality of their care are closely related to the speed of their diagnosis and treatment; this is because they are concerned that longer waits might allow time for their cancers to grow 25…”
Section: Introductionmentioning
confidence: 99%
“…Timely diagnosis of cancer has therefore been an important aim of healthcare providers across Europe 25. However, the challenge in deciding where and how to achieve this is substantial 26.…”
Section: Introductionmentioning
confidence: 99%
“…Participants saw the FDS as a way of clarifying when they could rightfully phone to chase test results, but the majority felt 28 days was too long to wait for suspected cancer, and they would contact providers sooner than this. Previous qualitative studies have shown that patients who went on to have a cancer diagnosis considered a 2-week wait to be too long, provoking anxiety 23 , 33. Awareness of current standards for diagnostic referral for cancer was low within the group, with both over- and underestimates of waiting timeframes reported by participants within discussions.…”
Section: Discussionmentioning
confidence: 88%
“…, Malmström et al . , Ziebland et al . ) that drew on cross country comparisons to highlight opportunities for service improvement, this article provides a sociological analysis of care, choice and medical authority in patients’ stories of their cancer diagnosis to further our understanding of the changing patient–doctor relationship.…”
Section: Introductionmentioning
confidence: 99%